2013
DOI: 10.1182/blood-2013-01-477687
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the symptom burden associated with the treatment of chronic myeloid leukemia

Abstract: • The MD Anderson SymptomInventory for CML can be used to collect patientreported symptoms for research and clinical practice.• Thirty percent of patients in chronic-phase CML and on TKIs experience moderate symptoms that interfere with daily functioning.We developed a module of the MD Anderson Symptom Inventory (MDASI) for patients with chronic myeloid leukemia (CML). To develop the MDASI-CML, we identified CMLspecific symptoms from qualitative interviews with 35 patients. A list of candidate symptoms was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 32 publications
3
77
0
2
Order By: Relevance
“…13 Importantly, the severity of TKI side effects tended to remain relatively constant over time. A study undertaken in imatinibtreated patients showed impaired physical and mental health status in patients ,60 years of age, whereas older CML patients on average had a health status comparable to age-matched controls.…”
Section: Problems With Ongoing Tki Therapymentioning
confidence: 99%
“…13 Importantly, the severity of TKI side effects tended to remain relatively constant over time. A study undertaken in imatinibtreated patients showed impaired physical and mental health status in patients ,60 years of age, whereas older CML patients on average had a health status comparable to age-matched controls.…”
Section: Problems With Ongoing Tki Therapymentioning
confidence: 99%
“…Таким образом, при комплексной оценке эф-фекта и безопасности терапии ХМЛ, помимо определения клинического эффекта и побочных ре-акций, важными составляющими являются качество жизни и профиль симптомов больного [15, [21][22][23][24][25].…”
Section: контакты: татьяна ивановна ионова Tation16@gmailcom в статьunclassified
“…26 Unlike the EORTC QLQ CML-24, this questionnaire has been devised to evaluate symptom burden (rather than QoL). The strength of this tool was the longitudinal analysis performed in the development process, which further supported validity data.…”
Section: Use and Area Of Applications Of Pro Instruments In CMLmentioning
confidence: 99%